2010
DOI: 10.1073/pnas.0910267107
|View full text |Cite
|
Sign up to set email alerts
|

UBR2 mediates transcriptional silencing during spermatogenesis via histone ubiquitination

Abstract: Ubiquitination of histones provides an important mechanism regulating chromatin remodeling and gene expression. Recent studies have revealed ubiquitin ligases involved in histone ubiquitination, yet the responsible enzymes and the function of histone ubiquitination in spermatogenesis remain unclear. We have previously shown that mice lacking the ubiquitin ligase UBR2, one of the recognition E3 components of the N-end rule proteolytic pathway, are infertile associated with meiotic arrest at prophase I. We here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 25 publications
3
68
1
Order By: Relevance
“…Spermatogenesis involves various histone modifications including ubiquitination, phosphorylation, methylation and acetylation (17). A previous study indicated that a high quantity of uH2A was detected in the pachytene stage of spermatocytes, by immunoblot and immunohistochemical analysis of wild-type mice testes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis involves various histone modifications including ubiquitination, phosphorylation, methylation and acetylation (17). A previous study indicated that a high quantity of uH2A was detected in the pachytene stage of spermatocytes, by immunoblot and immunohistochemical analysis of wild-type mice testes (18).…”
Section: Discussionmentioning
confidence: 99%
“…PRC1 mediates chromatin compaction (Francis et al 2004), and RNF2-mediated monoubiquitination of H2A is associated with gene silencing. Based on these views, ubiquitinated H2A on meiotic sex chromosomes has been considered to have functions in gene silencing (Baarends et al 2005;An et al 2010). In contrast, we revealed a novel role for ubiquitinated H2A in gene activation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…19 These outcomes indicate that a single component of the N-end rule pathway may be involved in multiple layers of regulatory circuits, probably in temporal cooperation with various downstream regulators of the pathway, such as the UBR proteins. The biological functions of these UBR proteins include the regulation of cardiovascular development, 17 chromosomal stability, 20 spermatogenesis, 21 oxygen sensing, 22 muscle wasting, [23][24][25][26] proteotoxic protein clearance, 27 hypertension, 28 neuronal tube formation, 29 bacterial/viral virulence, 30 and apoptosis. 31 More recent studies have suggested that the Arg/N-end rule pathway is also implicated in autophagy and mitophagy.…”
Section: Introductionmentioning
confidence: 99%